Torsion of an Accessory Hepatic Lobe with Embedded Gallbladder: In an 11-Month-Old Boy - Thakral, Chiman Lal; Shivalingam, Ganji; Dar, Faizan Manzoor; Thakral, Nimish (European Journal of Pediatric Surgery Reports, 2017)
An accessory lobe of the liver is a rare entity in clinical practice which is diagnosed incidentally. Infrequently, it may present as torsion with a clinical picture of an acute abdomen, a palpable mass, and may be associated with liver function abnormalities. Many of these patients have a history of previous surgery for congenital abdominal wall defects such as omphalocele. We present an extremely rare case of torsion of an accessory hepatic lobe in an 11-month-old male patient who presented in a state of shock. The infant underwent laparotomy and excision of the accessory lobe. Here, we aim to emphasize the importance of prompt management and early resection which is the cornerstone of a favorable outcome.
Keywords: accessory hepatic lobe; torsion of accessory liver lobe; omphalocele